Case Study of Supreme Court Decision Number 418 K / Pid / 2016 Against Criminal Perpetrators Participating in Making Fake Letters - Andriani, Irine; Santoso, Aris Prio Agus; Muftiyanto, R. Taufiq Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The problem that arises with medepleger in the crime of document forgery is that its application is not explicitly regulated in the Criminal Code regarding its punishment. Then a gap emerged between das sollen (the Criminal Code does not explicitly regulate the criminal offense of participating in making fake letters) and das sein (many people who commit crimes taking part in making fake letters), as in Supreme Court Decision Number 418 K/Pid /2016. This research aims to determine the regulation of the criminal act of forgery of letters in the Criminal Code and to determine the imposition of criminal sanctions against perpetrators of criminal acts who participate in the continuous production of fake letters. This research is a type of normative juridical research, with a statutory approach and a case approach. Research data relies on primary data in the form of statutory regulations and binding decisions and secondary data, namely library sources. As for the research results: the legal arrangements for inclusion in the Criminal Code are regulated in 55 paragraph 1 of the Criminal Code. Regulations for the act of falsifying letters are regulated in Chapter Overall, what is at the core of all forms of criminal acts of letter forgery are making fake letters, falsifying letters and using fake letters or forged letters. what is formulated in the Articles on falsification of letters is the action on the object or form of the letter. The imposition of criminal sanctions against perpetrators of criminal acts who participated in making fake letters which is carried out continuously in the Supreme Court Decision Number 418K / PID / 2016 is based on legal facts, whether through witness statements, defendant statements, or evidence, mitigating and aggravating matters. the defendant and based on juridical considerations. In this case the defendant committed the act by means of participation. With the fulfillment of the elements in article 263 paragraph 2 of the Criminal Code jo. Article 55 paragraph 1 of the Criminal Code means that the criminal act charged is legally and convincingly proven according to the law.